Evaluation of Warfarin Use in Cardiac Clinic Outpatients - Norisca A. Putriana; Taofik Rusdiana; Tina Rostinawati; Mohammad R. Akbar; Dika P. Destiani (Universitas Padjadjaran, Indonesia, 2022)
The use of warfarin was monitored using the International Normalized Ratio (INR) value. This study aims to determine the relationship between the patient’s demographic variables and INR, as well as the therapy result and differences in their INR value. A cross-sectional study was used with retrospective observational data collected by tracing secondary information of medical records from outpatients with heart disease on warfarin therapy at Dr. Hasan Sadikin hospital Bandung between 2016 to 2020. Subsequently, the difference in patients’ INR value was analyzed with the Mann-Whitney test based on dosage. At the same time, the relationship between demographic variables and INR was examined using the Chi-square test and Spearman correlation. The INR examination results in 192 subjects showed 124 patients (64.6%) reached the target with an average value of 2.37 ± 0.21 and a warfarin dose of 19.31 ± 6.25 mg weekly, while 68 (35.4%) had an average of 1.82 ± 0.73 and a dose of 20.24 ± 6.24 mg weekly. Subsequently, the difference test with Mann Whitney (p = 0.004) showed a variation in the INR value based on the warfarin dose. The Spearman correlation analysis results indicated a relationship between BMI (p = 0.009), daily (0.010), and weekly dose (0.008) on the INR value with the correlation coefficient of 0.188; 0.186; and 0.192; indicating a negative association with very weak correlation strength. This study showed that a majority of patients reached the INR value of 2-3, and the demographic variables associated with this ratio were BMI and warfarin dose. The decision to increase and decrease the warfarin dose is determined by INR value and BMI.